New molecular prognostic factors in patients with breast cancer - Bednarek, Andrzej; Płuciennik, Elżbieta; Kordek, Radzisław; Kusińska, Renata (Contemporary Oncology/Współczesna Onkologia, 2004)
Molecular classification of breast cancers features a group with an expression of luminal-type cytokeratins (cytokeratins 7, 8, 18, 19) and with an expression of basal-type cytokeratins (cytokeratins 5, 6, 14, 15, 17). There is subtype A with a strong expression of ERa and other genes connected with this profile, subtype B and C with a weaker expression of these genes in a group of the luminal-type breast cancer. On the other hand the basal-type cancers with an expression of cytokeratins 5/6 and 17 demonstrate no presence of estrogen receptors, a high expression of cyclin E, a low expression of P27/Kip are associated with a poor prognosis. There are some specific molecular alternations (LOH 5q and 4p) in this group and also includes cases of BRCA1 mutation carriers. The group with HER-2 amplification is separate, however it shares many elements with the basal-type breast cancer group. Another small group shows gene expression similar to the normal breast tissue. The DNA microarrays have also demonstrated that particular profiles of gene expression are characteristic in young woman breast cancers with different prognosis. Similarly, significant differences in gene expression were recognized for the resistance to antracyclins. It is expected that these results will be shortly useful in clinical practice.